Pelaksanaan Skrining Pre Eklampsia Berdasarkan Faktor Resiko Sedang Dan Tinggi Di Puskesmas Tapin Utara - Puteri, Dewi Ineke; Dona, Sismeri; Lathifah, Nur (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Pre-eclampsia screening in early pregnancy is effective in preventing pre-eclampsia. Screening has been implemented and the program has been running but the incidence of pre-eclampsia as a cause of maternal death in Indonesia. The purpose of the study was to determine the implementation of pre-eclampsia screening based on medium and high risk factors at the North Tapin Health Center. Quantitative descriptive research with retrospective approach. The data used is secondary data. Purposive sampling technique totaled 181 people. The implementation of pre-eclampsia screening based on moderate risk factors at the North Tapin Health Center according to univariate analysis in this study was completely filled as many as 47. 5% and 52.5% are filled quite completely. Moderate risk factors that are still filled quite completely from the lowest are risk factors for obesity before pregnancy (66.3), risk factor calculation MAP value > 90 (84.5%), Multiparous risk factors with pregnancy by new partners (95.0%) and proteinuria > +1 (97.2%) The implementation of pre-eclampsia screening based on high risk factors at the North Tapin Health Center is 100% complete